Comparison of clinical outcomes between cone beam CT-guided thermal ablation and helical tomotherapy in pulmonary metastases from hepatocellular carcinoma - Wang, Feihang; Fan, Shaonan; Shi, Qin; Zhao, Danyang; Sun, Huiyi; Sothea, Yav; Wu, Mengfei; Song, Huadan; Chen, Yi; Cheng, Jiemin; Zeng, Zhaochong; Yan, Zhiping; et al. (Frontiers in Oncology, 2022)
Objective: This retrospective study compares the clinical results of cone-beam CT (CBCT) guided thermal ablation with those of helical tomotherapy in hepatocellular carcinoma (HCC) patients with pulmonary metastases. Methods: A total of 110 patients from April 2014 to December 2020 undergoing thermal ablation or helical tomotherapy for pulmonary metastases were included in the study. The endpoints were local tumor progression-free survival (LTPFS), overall survival (OS), and complications. Univariate and multivariate analyses using the Cox proportional hazard model were conducted to identify independent factors (univariate: P<0.1; multivariate: P<0.05). Kaplan-Meier method was used to calculate the LTPFS and OS rates. Results: The results of 106 patients were taken into the final analysis. The 1-and 3-year LTPFS rates were 50% and 19% for the thermal ablation group, and 65% and 25% for the helical tomotherapy group. The median LTPFS in the thermal ablation group was 12.1 months, while it was 18.8 months in the helical tomotherapy group (P=0.25). The 1-and 3-year OS rates were 75% and 26% for the thermal ablation group, and 77% and 37% for the helical tomotherapy group. The median OS was 18.0 months in the thermal ablation group and 23.4 months in the helical tomotherapy group (P=0.38). The multivariate analyses found that α-fetoprotein (AFP) <400ng/mL (P=0.003) was significantly associated with better LTPFS. Tumor number <3 and AFP<400ng/mL were favorable prognostic factors for OS. There were no Grade 3-5 adverse events (AE) in both groups. Grade 2 was recorded in 3 patients (4.8%) in the thermal ablation group and 2 patients (4.7%) in the helical tomotherapy group. Conclusions: For pulmonary metastases from HCC, CBCT guided thermal ablation and helical tomotherapy provided comparable clinical effects and safety.